FROM THE STAGE TO THE COURTYARD: THE XUXA EFFECT, THE MEDIA IMAGINARY AND THE REINVENTION OF TEACHING BETWEEN SHOW AND LISTENING - Nery Carneiro, Everton; de Jesus Santana, Lousana (Revista Gênero e Interdisciplinaridade, 2025)
This article investigates the impact of the Xuxa effect on teacher formation and pedagogical practices in Brazilian basic education, focusing on childhood and early grades. The objective is to analyze how this media phenomenon — combining affection, performance, and consumption — helped consolidate a symbolic model of performative, aestheticized, and spectacularized teaching, in contrast to critical pedagogy based on listening and dialogue. The theoretical framework draws on authors such as Freire (1996), Debord (1997), Fischer (2006), Sodré (2006), and Nóvoa (2009), articulating critical pedagogy, the critique of the society of the spectacle, and cultural studies. The methodology is qualitative, with a theoretical-documentary nature and based on Foucauldian discourse analysis. Episodes of Xou da Xuxa, pedagogical materials, teacher autobiographies, and audiovisual records of classroom practices were analyzed, comparing media and pedagogical elements symbolically. Results indicate that the logic of spectacle reconfigured the educational imaginary, shaping the figure of the “entertainer teacher” and shifting the focus from critical listening to affective performance. The study concludes that teaching has been partially captured by the logic of image and enchantment, demanding an ethical and epistemological reinvention of educational practice.